A Combined Angelica gigas and Artemisia dracunculus Extract Prevents Dexamethasone-Induced Muscle Atrophy in Mice through the Akt/mTOR/FoxO3a Signaling Pathway - Hyun-Ji Oh; Heegu Jin; Byung-Yong Kim; Ok-Hwan Lee; Boo-Yong Lee (Cells, 2022)
Since skeletal muscle atrophy resulting from various causes accelerates the progression of several diseases, its prevention should help maintain health and quality of life. A range of natural materials have been investigated for their potential preventive effects against muscle atrophy. Here, ethanol extracts of Angelica gigas and Artemisia dracunculus were concentrated and dried, and mixed at a ratio of 7:3 to create the mixture CHDT. We then evaluated the potential for CHDT to prevent muscle atrophy and explored the mechanisms involved. CHDT was orally administered to C57BL/6 mice daily for 30 days, and dexamethasone (Dex) was intraperitoneally injected daily to induce muscle atrophy from 14 days after the start of oral administration. We found that CHDT prevented the Dex-induced reductions in muscle strength, mass, and fiber size, likely by upregulating the Akt/mTOR signaling pathway. In addition, CHDT reduced the Dex-induced increase in the serum concentrations of pro-inflammatory cytokines, which directly induce the degradation of muscle proteins. These findings suggest that CHDT could serve as a natural food supplement for the prevention of muscle atrophy.